Energy and protein requirement of replacement pullets - Albino, Luiz F. T.; Fialho, Flavio B.; Bellaver, Claudio; Hara, Claudete; Paiva, Guilherme J. (Pesquisa Agropecuaria Brasileira, 1994)
The aim of this work was to estimate the energy and protein requirements for maintenance and gain of replacement pullets. One thousand and four hundred birds were used, 700 of which were CNPSA Leghorn line birds (EMB), being the remaining Lohmann (LH) comercial line birds. The experimental design was completely random, with four treatments, two lines, and seven replicates of 25 birds each, placed on floor boxes. The treatments were four levels of intake (T1 = ad lib; T2 = 85% of T1; T3 = 70% of T1; T4 = feed for maintenance). Carcass analysis obtained from comparative slaughtering were used for the estimation of the daily metabolizable energy (ME, kcal/d) and nitrogen (N, g/d) requirements 0,75 as function of metabolic weight (MW, kg0,75) and carcass energy (CE, kcal) and nitrogen (CN, g) deposition. The resulting estimated equations were: ME = 142.0 MW + 2.114 CE and N = 0.580 MW + 1.798 CN for EMB; ME = 163.6 MW + 1.762 CE and N = 0.762 MW + 1.616 CN for LH.